2015
DOI: 10.1007/s10396-015-0627-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sonographic image analysis for hepatic nodules: a pilot study

Abstract: Quantitative image analysis for ultrasonic images of hepatic nodules may correlate with subjective judgment in predicting malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The range of gray values between minimum and maximum was divided into 256 bins. The method of image analysis used in this study was previously described 10 . Interobserver agreement was confirmed in the previous report.…”
Section: Methodssupporting
confidence: 66%
See 3 more Smart Citations
“…The range of gray values between minimum and maximum was divided into 256 bins. The method of image analysis used in this study was previously described 10 . Interobserver agreement was confirmed in the previous report.…”
Section: Methodssupporting
confidence: 66%
“…To date, several studies of quantitative image analyses for morphologic features of HCC have been published 3,7–15 . Our previous study reported that the circularity and minimal gray value were predictive factors of malignancy to differentiate HCC from hepatic hemangioma, and an image analysis improves the accuracy of diagnosis 10 . In other previous studies using image analyses, HCC was divided into 3 groups according to the shape detected by contrast‐enhanced computed tomography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subcutaneous tissue, which underlies the dermis and appears as a hypoechoic area compared with the overlying reticular dermis, has already been shown to be thickened in oedema (Caggiati, 2016). Third, echogenicity within the subcutaneous layer was measured using image analysis software (ImageJ; National Institutes of Health) (Matsumoto et al, 2015). Digital Imaging and Communications in Medicine (DICOM) images of the subcutaneous layer were analysed on an offline personal computer equipped with the ImageJ software, and echogenicity was measured as a grey‐scale value ranging from 0 (absolute black) to 255 (absolute white) (pixel intensity, 256 grey levels per pixel).…”
Section: Methodsmentioning
confidence: 99%